Conceptual Sim-Heuristic optimization algorithm to evaluate the climate impact on reservoir operations - Lai V.; Huang Y.F.; Koo C.H.; Najah Ahmed A.; El-Shafie A. (Elsevier B.V., 2023)
Climate change; Climate models; Digital storage; Neural networks; Reservoirs (water); Water resources; Coupled Model Intercomparison Project; Coupled model intercomparison project 5; Down-scaling; General circulation model; Klang gate dam; Metaheuristic; Optimisations; Reservoir operation; Simulation; Support vector regressions; Optimization; climate change; climate effect